2016
DOI: 10.3168/jds.2016-10985
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of pasture versus indoor feeding systems on raw milk composition and quality over an entire lactation

Abstract: The aim of this study was to investigate the effects of different feeding systems on milk quality and composition. Fifty-four multiparous and primiparous Friesian lactating cows were divided into 3 groups (n=18) to study the effects of 3 feeding systems over a full lactation. Group 1 was housed indoors and offered a total mixed ration diet (TMR), group 2 was maintained outdoors on a perennial ryegrass pasture (referred to as grass), and group 3 was also grazed outdoors on a perennial ryegrass/white clover past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
285
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(316 citation statements)
references
References 49 publications
22
285
2
1
Order By: Relevance
“…The pasture-based system can ensure the absence of late lactation milk from any individual cow or group of cows in a herd by imposing a specific cow dryingoff (cessation of milk) strategy (Guinee and O'Brien, 2010), whereas the separation of late lactation milk is more difficult with the year-round calving pattern normally associated with confined milk production systems. O'Callaghan et al (2016) reported that a principal component analysis of the average fatty acid profiles showed a quite distinct and clear separation of milks throughout lactation in relation to the two feeding regimes. The study makes an important contribution to identifying how pasture-derived milk can be verified by fatty acid profiling.…”
Section: Pasture-based Milk Productionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pasture-based system can ensure the absence of late lactation milk from any individual cow or group of cows in a herd by imposing a specific cow dryingoff (cessation of milk) strategy (Guinee and O'Brien, 2010), whereas the separation of late lactation milk is more difficult with the year-round calving pattern normally associated with confined milk production systems. O'Callaghan et al (2016) reported that a principal component analysis of the average fatty acid profiles showed a quite distinct and clear separation of milks throughout lactation in relation to the two feeding regimes. The study makes an important contribution to identifying how pasture-derived milk can be verified by fatty acid profiling.…”
Section: Pasture-based Milk Productionmentioning
confidence: 99%
“…The study makes an important contribution to identifying how pasture-derived milk can be verified by fatty acid profiling. An extended version of the study of O'Callaghan et al (2016) is currently ongoing and is focussed on identifying and comparing differences in milk (in relation to composition, sensory value, volatiles and processability) and milk products (butter, cheese, whole milk powder and infant formula) produced from grass and TMR diets. The findings can then be used to benchmark the profile of milk produced from the Irish grass-based system against that of TMR-based systems in use in the USA and other EU countries.…”
Section: Pasture-based Milk Productionmentioning
confidence: 99%
See 3 more Smart Citations